Failure analysis on unexpected wall thinning of heat-exchange tubes in ammonia evaporators. (April 2015) - Hu, Shi-Meng; Wang, Sheng-Hui; Yang, Zhen-Guo
Highlights: Unexpected wall thinning of heat-exchange tubes in ammonia evaporators was detected. Comprehensive investigations to figure out root cause of failure were conducted. Serious material degradations were primarily ascribed to multiple corrosion factors. Practical prevention measures were proposed for avoiding similar failure incident. Abstract: A failure incident of heat-exchange tubes in ammonia evaporators, which suffered from unexpected wall thinning after only one-year service with respect to their original design lifetime of fifteen years, was reported and carefully analyzed. After overall inspection, many tube walls in the evaporators were found to experience severe degradations at both sides with distinct corroded defects and general cracking of corrosion layers. Thus, comprehensive investigations including external appearance, microscopic morphology and chemical composition were carried out by using a series of characterization methods. The analysis results demonstrated that the unexpected wall thinning of tubes was primarily ascribed to multiple corrosion factors including uniform corrosion, pitting and interaction behavior between them. Relative failure mechanisms were discussed in detail and prevention measures were also proposed for ammonia evaporators under similar operating condition.